Penyebab Ekuitas Negatif: Uji Signifikansi Pada Laba Bersih dan Nilai Utang - Suwandi Suwandi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This causal study aims to analyze the effect of net income and debt value on negative equity in companies with a special label “tato” listed on the Indonesia Stock Exchange (IDX) in 2020. This study involved 59 companies and as many as 22 companies were selected based on sample criteria. 22 observational data. The data collection technique uses the documentation method in the form of financial reports that have been published through www.idx.co.id. The data that has been collected is processed using the SPSS version 23 program. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that, partially net income has a positive and insignificant effect on negative equity, while the value of debt has a negative and significant effect on negative equity. Meanwhile, simultaneously net income and debt value have a significant negative effect on equity. Following up on the findings of this study, the measurement of the causes of negative equity must be identified early on and analyzed carefully so that it can be controlled so as to increase the company's equity value.